Doubled Identity in the Thematic Repertoire of Pier Paolo Pasolini from Friulian Poetry to Divina Mimesis and Petrolio (Altre Modernità, 2025)
Within Pier Paolo Pasolini's repertoire, the thematic field of doubled identity (Fusillo, 1998) is central. In this perspective, this paper aims to analyze some related themes such as that of Narcissus and the double in Poesie a Casarsa, La meglio gioventù, Dal diario, Venti pagine di diario, L'Usignolo della Chiesa Cattolica, La Divina Mimesis and Petrolio. The investigation involves analyzing the reflections in the texts from the 1940s and 1950s, which aim to describe the process of self-knowledge, and the duplications found in the last two works, which respond to the cognitive and creative concerns developed by Pasolini in the 1960s and 1970s, expressing a deeper reflection on the self, its relationships, and the evolution of socio-historical reality.
Keywords: Pasolini; thematic field; Narcissus; repertoire